Hot deformation behavior and dynamic recrystallization kinetic modeling of the Mg–7Gd–3Y–1Zn–0.5Zr alloy - Chen Zhong; Yongjun Li; Qichi Le; Minglong Ma; Xinggang Li; Guoliang Shi; Jiawei Yuan; Zhaoqian Sun; Kui Zhang (Journal of Materials Research and Technology)
In this study, the microstructure evolution on hot deformation was investigated and a dynamic recrystallization (DRX) kinetic model was constructed based on the hot deformation behavior of the homogenized state Mg–7Gd–3Y–1Zn–0.5Zr (VW73B) alloy within 713–773 K and 0.01–0.1 s−1. The DRX critical strain reduced when the deformation temperature (T) increased and increased when the strain rate (ε˙) increased. The variation trend of the DRX volume fraction was inversely proportional to the critical DRX strain. The constructed DRX kinetic model was modified by introducing a compensation factor; the modified model showed a mean absolute deviation of the DRX volume fraction of 1.8%. Combined with the microstructure analysis, it can be found that the Long Period Stacking Ordered (LPSO) phase is able to promote DRX during the hot deformation, but its ability to promote DRX is less pronounced than that of grain boundaries. At the block-shaped LPSO phase interface, the grain boundary arched by strain induction provided a nucleation site for DRX, enabling discontinuous dynamic recrystallization (DDRX). At the lamellar LPSO phase interface, continuous dynamic recrystallization (CDRX) occurred predominantly through the continuous migration and merging of subgrains, resulting in the formation of DRX grains. The results of this study could guide future research on the DRX of the VW73B alloys with varied applications.